PENGEMBANGAN BUDAYA KEAGAMAAN MELALUI MANAJEMEN DOA BERSAMA DAN BACA AL QURAN PRA-KEGIATAN PEMBELAJARAN SERTA DAMPAKNYA TERHADAP PERILAKU SISWA - Abdul Rouf; Ali Sukamtono; Didik Siswandi (FAI- Undar, 2017)
The Development of Religious Culture is required to habituate the students with religious values to make them unseparated parts of students‟ daily behaviour either in school or society environment.This research was implemented at SMAN 1 Nglames, Madiun. Kind of research used qualitative with Action Research Approach (School Action Research). The researcher‟s perspective involves directly and holistically as a participant in this research. Data collecting used an observation, interview, and documentation.The result is the development of Religious Culture through the management of self habituation in praying collectively and reading Al-Quran before the teaching and learning process starts in SMAN 1 Nglames Madiun can give positive impact towards students‟ behaviour in particular and school inhabitants in general like the students‟ awareness to respect, be tolerant, and have religious characteristics. For example, the awareness to wear “hijab” as the muslim, express greeting, and shake the teachers‟ hand. Students are getting accustomed to praying Dhuha at recess and praying Dhuhur in conggregation. So, there is good increase of politeness and obedience in worship.